Dorsal medial prefrontal cortex contributes to conditioned taste aversion memory consolidation and retrieval - González, María Carolina (2015)
The medial prefrontal cortex (mPFC) is known for its role in decision making and memory processing, including the participation in the formation of extinction memories. However, little is known regarding its contribution to aversive memory consolidation. Here we demonstrate that neural activity and protein synthesis are required in the dorsal mPFC for memory formation of a conditioned taste aversion (CTA) task and that this region is involved in the retrieval of recent and remote long-term CTA memory. In addition, both NMDA receptor and CaMKII activity in dorsal mPFC are needed for CTA memory consolidation, highlighting the complexity of mPFC functions.